Rozwiąż układy równań :
a) 3x -1=y-2
4x-3=-2(y-2)
b) 2(x+y)-(x-1)=y+2

... x+y=1
c) ½(x-1)+y=-2½
x-7=1-y

Rozwiązanie

A) 3x -1=y-2 (wyznaczam x przenosze -1 na druga strone)
4x-3=-2(y-2)
3x=y-2+1( dziele przez 3)
4x-3=-2(y-2)
x=y-1/3
4* y-1/3=-2y+4(mnożymy przez 3)
x=y-1/3
4*(y-1)=3(2y+4)
x=y-1/3
4y-4=6y+12
x=y-1/3
4y-6y=12+4
x=y-1/3
-2y=16(dzielimy na -2)
x=y-1/3
y=-8
x=-8-1/3
y=-8
x=-3
y=-8

A) 3x -1=y-2
4x-3=-2(y-2)
3x-y=-1
4x-3=-2y+4
3x-y=-1/*2
4x+2y=7
6x-2y=-2
4x+2y=7
10x=5//10
x=½
2-2y=7
-2y=5/-2
y=2½
b) 2(x+y)-(x-1)=y+2
x+y=1
2x+2y-x+1=y+2
x+y=1
x+y=1/*-1
x+y=1
-x-y=-1
x+y=1
0=0
równanie tożsamościowe
c) ½(x-1)+y=-2½
x-7=1-y
½x-½+y=-2½/*2
x+y=8
x-1+2y=-5
x+y=8
x+2y=-4/*-1
x+y=8
-x-2y=4
x+y=8
-y=12/*-1
y=-12
-12+x=8
x=20

PODOBNE ZADANIA: